2011
DOI: 10.4067/s0716-078x2011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de distribución geográfica de la riqueza de especies de roedores de la tribu Oryzomyini (Rodentia: Sigmodontinae) en Sudamérica: Evaluando la importancia de los procesos de colonización y extinción

Abstract: RESUMENLa tribu de roedores Oryzomyini es la más diversa dentro de la subfamilia Sigmodontinae. Está constituida por 120 especies y 31 géneros, de las cuales 83 son endémicas del continente sudamericano. Este grupo exhibe una extensa distribución que abarca toda la región Neotropical, caracterizada por la presencia de una mayor riqueza en la Amazonia con una disminución monotónica hacia el sur y norte de Sudamérica. Este es un patrón bastante conocido en la mayoría de los taxones, por lo que se han propuesto v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…Valencia- Pacheco et al (2011), evaluating patterns of diversity for the tribe, reported the existence of a latitudinal gradient in the number of species of Oryzomyini with a marked decrease in diversity towards the south and northwards from the Amazon Basin, and together with the Amazon comprises the most diverse area of South America. In their Source-Sink model, the Amazon region has served as a "source" (a kind of 'center of origin' for the tribe) from which species dispersed and colonized new environments.…”
Section: Diversity Patterns and Endemismmentioning
confidence: 99%
See 2 more Smart Citations
“…Valencia- Pacheco et al (2011), evaluating patterns of diversity for the tribe, reported the existence of a latitudinal gradient in the number of species of Oryzomyini with a marked decrease in diversity towards the south and northwards from the Amazon Basin, and together with the Amazon comprises the most diverse area of South America. In their Source-Sink model, the Amazon region has served as a "source" (a kind of 'center of origin' for the tribe) from which species dispersed and colonized new environments.…”
Section: Diversity Patterns and Endemismmentioning
confidence: 99%
“…Despite these deficiencies, based on substantive advances in our understanding of the geographical distribution, taxonomy and phylogenetic relationships, several authors have hypothesized the place and pattern of geographical diversification, as well as the time of origin and radiation patterns, of this group (Simpson, 1950(Simpson, , 1969Hershkovitz, 1966Hershkovitz, , 1972Patterson & Pascual, 1968Savage, 1974;Baskin, 1978Baskin, , 1986Marshall, 1979;Reig, 1980Reig, , 1984Reig, , 1986Jacobs & Lindsay, 1984;Slaughter & Ubelaker, 1984;Steppan, 1995;Engel et al, 1998;Smith & Patton, 1999;Pardiñas et al, 2002;Steppan et al, 2004;Barros et al, 2009;Valencia-Pacheco et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta dinámica como tal, puede ser estudiada en base a análisis de anidamiento de la riqueza en el paisaje tanto a escala espacial (e.g. Moreno et al 2008, Valencia-Pacheco et al 2011) como temporal (e.g. Azeria & Kolasa 2008.…”
Section: Introductionunclassified
“…[1-16] Las ratas del género Hylaeamys (Rodentia: Cricetidae) habitan los bosques húmedos tropicales Amazónicos hasta los subtropicales Andinos, desde Venezuela y Guyana hacia el sur por el Amazonas hasta el este de Brasil y Paraguay, alcanzando los 1500 m de altitud [1][2][3][4][5]. El género está representado por siete especies [5], tres de ellas presentes en Ecuador [1,3], de las cuales Hylaeamys yunganus Rata de Tierras Bajas de las Yungas se distribuye en la Amazonía y estribaciones orientales de los Andes entre 200 y 1581 m de altura [1- 3,6].…”
unclassified